Comparison of Rubber as Aggregate and Rubber as Filler in Concrete - Mohd Mustafa Al Bakri, Abdullah; Syed Nuzul Fadzli Syed Adam; M. D. Abu Bakar; K. W Leong (Universiti Malaysia Perlis (UniMAP), 2008)
Organized by Universiti Malaysia Perlis (UniMAP), 9th - 12th June 2007 at Park Royal Hotel, Penang.